Bioinspired polymer nanoparticles omit biophysical interactions with natural lung surfactant. Issue 7 (9th August 2019) - Beck-Broichsitter, Moritz; Bohr, Adam
Abstract: Herein, we report the attenuated impact of bioinspired nanoparticles on the essential function of lung surfactant. Colloidal particles made from poly(lactide) caused a significant loss of surfactant protein B (and C) from a natural lung surfactant accompanied by a decline in surface activity under static conditions and surface area cycling. No such perturbation of lung surfactant composition and function was observed for polymer nanoparticles coated with bioinspired poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC). More specifically, increasing the PMPC-coating layer thickness (≥3 nm) and density (dense conformation, distance of individual polymer chains of ≤3 nm) on the polymer nanoparticle surface diminished bioadverse events. PMPC-coated poly(lactide) nanoparticles provoked a less severe perturbation of the utilized lung surfactant when compared to colloidal counterparts coated with poly(ethylene glycol). Overall, a steric shielding of colloidal drug delivery vehicles with bioinspired PMPC can be considered as a valuable approach for the rationale development of biocompatible nanomedicines intended for lung delivery.